EGO/Speaker deixis: Ego-Centered Motion Metaphors of Time between Arabic and English – A Comparative Corpus-based Study - Dhifallah, Asma (fi=Turun yliopisto|en=University of Turku|, 2024)
Using a corpus cognitive-linguistic approach, the present study examines the deictic composition of Ego-centered motion metaphors of time (EMTs) in Arabic and English. EMTs are metaphors that describe the passage of time based on the conception of spatial motion, using a deictic perspective, e.g. Summer is coming, or We are approaching summer. The study paradigm addresses the deictic composition of EMTs from a comparative perspective and takes the finite verb expression as a unit of analysis, considering it to be at the intersection of a variety of veridical and metaphorical elements. To this aim, the study analyzes 2200 EMT lines by searching 44 different COME and GO verb expressions in Arabic and English. The current inquiry identifies several key findings: First, the analysis systematically distinguishes between Ego, the experiencer of the Motion Scenario, and the Speaker, the narrator of the Motion Scenario. This distinction is central to expressing a diverse range of metaphors and explains our conceptual ability to ‘go back in time’. Next, the study presents deictic subsystems based on the interaction of tense with viewpoint, lexical, and nominal aspects. The analysis indicates a major distinction between the two languages: English, using a tense system, is found to refer to both Ego’s ‘now’ and the Speaker’s present systematically in most cases; while Arabic, which is based on the dichotomy of the perfective and the imperfective, indicates Ego’s ‘now’ categorically but does not systematically relate the Motion Scenario to the time of speech. Finally, for each language, the usage distinctions among similar expressions are tested using a Random Forest statistical model. The resulting predictions indicate that verb expressions with similar conceptual meanings exhibit distinctive patterns of usage.

Ego-/puhujadeiksis: Egokeskiset ajan liikemetaforat arabiassa ja englannissa – vertaileva korpuspohjainen tutkimus Tutkimuksessa tarkastellaan kognitiivisen kielitieteen ja korpuslingvistiikan menetelmiä hyödyntäen arabian ja englannin kielen egokeskisten ajan liike-metaforien (EAL) deiktistä koostumusta. Tällaiset metaforat kuvaavat ajan kulu-misen spatiaalisen liikkeen kaltaisena ilmiönä hyödyntäen deiktistä näkökulmaa, esim. Kesä tulee tai Lähestymme kesää. Analyysin perusyksiköksi on valittu finiittiverbi-ilmaus, jonka voi katsoa olevan useiden merkitykseltään kirjaimellisten ja kuvaannollisten ajanilmaisukeinojen leikkauspisteessä. Aineistona analysoidaan 2200 löydetystä EAL-rivistä poimimalla 44:ää erilaista TULLA- tai MENNÄ-merkityksistä verbirakennetta sekä arabian- että englanninkielisistä korpusaineis-toista. Tutkimus uudistaa alan tutkimusperinnettä ja nostaa esille uusia näkökulmia. Ensinnäkin analyysissa erotetaan systemaattisesti toisistaan ego, liikeskenaarion kokija, ja puhuja, liikeskenaarion kertoja. Eronteko on olennainen, kun tarkastellaan erilaisten metaforisten merkitysten ilmaisemista ja selitetään ihmisen kykyä kielellisen käsitteistyksen avulla ”palata ajassa taaksepäin”. Tutkimuksessa tarkas-tellaan myös deiktisiä osajärjestelmiä, jotka ilmentävät ajasta tehdyn käsitteistyksen vuorovaikutusta yhtäältä tilanteeseen valitun näkökulman, toisaalta ilmauksen leksikaalisen ja nominaalisen aspektin kanssa. Analyysi osoittaa selviä eroja kahden tutkitun kielen välillä. Englanti, joka käyttää kieliopillista tempusjärjestelmää, ilmaisee järjestelmällisesti sekä egon ’nyt’-hetken että puhehetken mukanaoloa ja asemaa tilanteessa. Arabiassa ajan ilmaisemisen kielioppi taas perustuu perfek-tiivisen ja imperfektiivisen aspektin vastakohtaisuuteen. Se osoittaa egon ’nyt’-hetken aseman mutta ei liitä liikeskenaariota systemaattisesti puhehetkeen. Lisäksi kummastakin kielestä selvitetään metaforisten ajanilmausten käyttöeroja satunnais-metsänä tunnetun tilastomallin avulla. Tehdyt havainnot osoittavat, että verbi-ilmauksilla, joilla on samanlainen käsitteellinen merkitys, on toisistaan selvästi erottuvia käyttömalleja.